Arabic oration : art and function - Qutbuddin, Tahera (Brill, 2019)
In Arabic Oration: Art and Function, a narrative richly infused with illustrative texts and original translations, Tahera Qutbuddin presents a comprehensive theory of this preeminent genre in its foundational oral period, 7th-8th centuries AD. With speeches and sermons attributed to the Prophet Muḥammad, ʻAlī, other political and military leaders, and a number of prominent women, she assesses types of orations and themes, preservation and provenance, structure and style, orator-audience authority dynamics, and, with the shift from an oral to a highly literate culture, oration 's influence on the medieval chancery epistle. Probing the genre's echoes in the contemporary Muslim world, she offers sensitive tools with which to decode speeches by mosque-imams and political leaders today."-- Provided by publisher.
Keywords: Arabic language -- Rhetoric.; Sermons, Arabic -- History and criticism.; Speeches, addresses, etc.; Arabe (Langue) -- Rhétorique.; Discours.; speeches (documents); LITERARY CRITICISM / African; Arabic language -- Rhetoric; Sermons, Arabic; Criticism, interpretation, etc.